2021
DOI: 10.1093/hropen/hoab043
|View full text |Cite
|
Sign up to set email alerts
|

The role of endometrial B cells in normal endometrium and benign female reproductive pathologies: a systematic review

Abstract: STUDY QUESTION What are the similarities and differences in endometrial B cells in the normal human endometrium and benign reproductive pathologies? SUMMARY ANSWER Endometrial B cells typically constitute less than 5% of total endometrial CD45+ lymphocytes, and no more than 2% of total cells in the normal endometrium, and while their relative abundance and phenotypes vary in benign gynaecological conditions current evidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 98 publications
(172 reference statements)
0
13
0
2
Order By: Relevance
“…As both EM and EPs are estrogenic diseases, the correlation between their occurrence has always been a hotspot in clinical research. It has been reported that most infertile patients with EM are accompanied by EPs, suggesting that EM is related to the occurrence of EPs [ 24 ]. Evidence has shown that EM syndrome in infertile patients is positively correlated with the occurrence of EPs [ 25 ], indicating that there may be mutual promotion between the pathological changes of EM and EPs in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…As both EM and EPs are estrogenic diseases, the correlation between their occurrence has always been a hotspot in clinical research. It has been reported that most infertile patients with EM are accompanied by EPs, suggesting that EM is related to the occurrence of EPs [ 24 ]. Evidence has shown that EM syndrome in infertile patients is positively correlated with the occurrence of EPs [ 25 ], indicating that there may be mutual promotion between the pathological changes of EM and EPs in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…The function of B cells within the endometrium is not well established, as was concluded in a systematic review by Shen et al. ( 63 ). However, it is possible that the B cells within LAs function as well-placed antigen presenting cells to the surrounding T cells, as they express activation markers such as CD69, HLA-DR and CD83 to a higher degree than their peripherally derived counterparts ( 65 ).…”
Section: Immunity In the Normal Endometriummentioning
confidence: 99%
“…The phagocytic cells of the innate immune system – granulocytes, monocytes and macrophages, collectively make up 25% of the CD45 + endometrial immune milieu, whereas B cells are comparably rare regardless of hormonal cycle stage, at no more than 5% ( 17 , 39 , 43 , 63 ). Endometrial B cells exist primarily within LAs, but have also been detected in the stroma ( 45 , 64 ).…”
Section: Immunity In the Normal Endometriummentioning
confidence: 99%
“…The eutopic endometrium in women with endometriosis shares several common immunological characteristics with that in CE. For example, one feature of the eutopic endometrium in women with endometriosis is unusual infiltration of CD138(+) ESPCs and CD20(+)/CD5(+)/HLA-DR(+) B cells; these are typical immunocompetent cells observed in CE, but are sparse in the nonpathological endometrium [ 4 ]. Some studies suggest that these unusual ESPCs and endometrial B cells potentially play a role in the proliferation and survival of the other endometrial cell components.…”
Section: Challenges In Clinical Management Of Cementioning
confidence: 99%
“…By contrast, antibody-bearing lymphocytes of the B cell lineage are a rare leukocyte subpopulation found in the nonpathological human endometrium. Under a physiological condition, endometrial B cells account for approximately 3% of all endometrial lymphocytes and no more than 2% of all endometrial cells throughout the menstrual cycle [ 4 ]. Some CD138(+) endometrial stromal plasmacytes (ESPCs) can occasionally be seen in the stromal compartments.…”
Section: Introductionmentioning
confidence: 99%